Estudio de prefactibilidad para la instalación de una planta de producción de calzado deportivo hecho a base de plástico reciclado y látex de shiringa (Hevea brasiliensis) - Guerra Granados, Diego Martin (2022)
This work has the title of "Pre-feasibility study for the installation of a production plant for sports footwear made of recycled plastic and rubber latex", which aims to create an eco-friendly product by adding the variable ecology in the process of shoe production and the lack of an environmental culture in society. Currently, few companies do not worry about producing this type of product. Therefore, the plant will use natural resources optimally and "discarded plastic input" in a sustainable manner. Our product will be aimed at men and women from Lima Metropolitana, with an age range between 18 to 50 years old, belonging to socioeconomic sectors B and C, with a lifestyle oriented towards sports activities such as running, training in the gym, among others, in addition to feeling identified with the protection of the environment. The calculated demand is 615 715 pairs of shoes for the last year of the project, which will be distributed in boxes to department stores (Saga Falabella and Ripley) with a sales value of S/ 177 per pair of shoes. The location of the plant will be in the department of Lima, province of Lima, district of Lurín. This plant will have 2221 m2, will have an installed capacity of 523 688 pairs per year and will employ 54 operators and 60 workers in the administrative area. The initial investment for this project is S/ 15 300 158, which will be financed 50% by bank loan and 50% by own capital. In addition, the project is economically and financially viable, since VANE and VANF are positive and have a value of S/ 15 975 316 and S/ 17 533 627 respectively. On the other land, the TIRE and TIRF have a value of 45,07% and 61,67% respectively, being higher than the opportunity cost (COK) of 18,73% which reflects how profitable the project is.